THE CONTENTS OF INORGANIC COMPONENTS IN SELECTED POLISH AND ROMANIAN HERBAL TEAS INFUSIONS - Kończyk, Joanna; Michalski, Rajmund; Muntean, Edward; Lasoń, Wojciech; Gęga, Jerzy (Polish Journal of Natural Sciences, 2023)
Herbal teas are consumed due to their health properties that largely result from the contents of the organic and inorganic compounds in them. The aim of this study was to analyze the contents of the main inorganic ions (F -, Cl -, NO3-, PO43-, SO42-, Na+, K+, Mg2+, Ca2+) and trace metals (Cr, Mn, Fe, Ni, Cu, Zn, Cd, Al, Pb, Co) in infusions prepared from popular herbal teas available in the Polish and Romanian markets. Ion chromatography with conductivity detection and microwave plasma-atomic emission spectroscopy were applied for this purpose. It was established that in some instances, several herbal teas exhibit higher concentrations of hazardous analytes, such as nitrate, cadmium, lead, or chromium. The chemometric evaluation of the studied teas was carried out and the common traits and differences were found.